Location of Diaspora in V.S. Naipaul’s A Bend in the River - Mishra, Sanjay Kumar (KMC Research Journal, 2017)
The paper explores the traumatic experiences of diaspora in V. S. Naipaul’s A Bend in the River. It shows how immigrants turn vulnerable in a newly decolonized world. It argues that people suffer from identity crisis when they are culturally and geographically alienated. Identity is inextricably bound up with the notion of location. It analyses the traumatic experiences of diaspora problem of making identity, finding and making location are revealed through Naipaul’s writing. It brings to light the expression of identity in diaspora belonging and alienation diaspora, exile, dislocation and displacement.